Hazardous ingredients in cosmetics and personal care products and health concern: a review - R., Siti Zulaikha; Syed Ismail, Sharifah Norkhadijah; Praveena, Sarva Mangala (Scientific & Academic Publishing, 2015)
Increasing demand of cosmetics all over the world from teen to adult has increased awareness related to safety issue. The objective of this paper is to indicate the ingredients that possess health effect that can be found in cosmetics and personal care products. The ingredient was segmented to three parts which are preservatives, fragrances and heavy metal impurities. The related paper was reviewed in terms of the chemicals that commonly identified in the cosmetic and personal care product. This paper also highlighted the health risk possesses by such ingredients in the products. From the papers reviews, many chemicals remained arguable in term of safety and its presence in the products. The chemicals are either added for it intentional purposes or appears unintentionally due to the nature of chemical itself or due to the manufacturing processes. It is suggested that consumers aware over the ingredients used in their cosmetic and personal care products and the side effects it possesses.